2004
DOI: 10.1142/s0219265904001027
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Distributed Nonblocking Checkpointing

Abstract: Coordinated checkpointing has low stable storage requirements and simplifies the recovery process by reserving a set of consistent global checkpoints. Unfortunately, most algorithms that were proposed either incurred a high communication overhead or blocked all processes. Then, a coordinated algorithm was presented which was nonblocking and which forced only a subset of all processes to participate in a checkpointing event. This algorithm was shown to create inconsistencies in some situations and new algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Ni et al [61] have shown that the Cao-Singhal algorithm [20] may lead to inconsistencies during concurrent executions. The authors [61] also updated the algorithm proposed in [20] to allow concurrent executions. The number of useless checkpoints in [20] may be exceedingly high in some situations [48].…”
Section: Related Workmentioning
confidence: 99%
“…Ni et al [61] have shown that the Cao-Singhal algorithm [20] may lead to inconsistencies during concurrent executions. The authors [61] also updated the algorithm proposed in [20] to allow concurrent executions. The number of useless checkpoints in [20] may be exceedingly high in some situations [48].…”
Section: Related Workmentioning
confidence: 99%
“…In case of concurrent initiations, multiple triggers need to be piggybacked on normal messages [26]. Trigger contains the initiator process identification and its csn.…”
Section: Multiple Concurrent Initiationsmentioning
confidence: 99%
“…This will waste the scarce resources of the mobile distributed system. (ii) In case of concurrent initiations, multiple triggers need to be piggybacked on normal messages [23]. Trigger contains the initiator process identification and its csn.…”
Section: Multiple Concurrent Initiationsmentioning
confidence: 99%
“…Concurrent executions of the algorithm are allowed in [5]. W. Ni et al [23] have shown that this algorithm [5] may lead to inconsistencies during concurrent executions.…”
Section: Evaluation Of the Proposed Hybrid Algorithmmentioning
confidence: 99%